Policies of Credit Restructuring Relaxation as Moderation Variable on the Relationship between Financial Ratios and Banking Performance in Indonesia - Cita Pelangi Putri Sulistyoadi (Quantitative Economics and Management Studies, 2024)
This study investigates the impact of Indonesia's newly implemented restructuring relaxation policies as moderating variables on the banking sector's performance. Utilizing panel data regression analysis on a sample of 105 banks from 2017 to 2022, the research examines the relationships between non-performing loans (NPL), loan loss provisions (LLP), efficiency ratios, and bank return on assets (ROA). The findings indicate that prior to the policy implementation, the efficiency ratio negatively affected government banks' ROA, while both LLP and the efficiency ratio negatively impacted private and foreign banks' ROA. Post-implementation, the interaction between these policies and each variable (NPL, LLP, and efficiency ratio) was found to be significant for government banks, whereas none of them showed significance for private or foreign banks. This research contributes to understanding financial regulation dynamics and provides insights for policymakers and banking institutions navigating market complexities.